2021
DOI: 10.1007/s00520-021-06554-6
|View full text |Cite
|
Sign up to set email alerts
|

Depression, hope and social support among older people with cancer: a comparison of Muslim Palestinian and Jewish Israeli cancer patients

Abstract: Objectives: Studies concerning the psychosocial aspects of cancer diagnosis and treatment among older Muslim patients are scarce. The goal of this research was to compare depression, hope, and perceived social support between older Muslim Palestinians and Jewish Israelis diagnosed with cancer.Design: The study sample included 149 Muslim Palestinian and 122 Jewish Israeli cancer patients. Outcome measures: Self-administered measures of depression (5-Item Geriatric Depression Scale) and perceived social support … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…Regarding educational level, we found that cancer patients with low educational levels had more depression, which is similar to the findings of other studies 31,32 . However, other publications did not show a significant difference between the two variables of education level and depression 19,33 .…”
Section: Discussionsupporting
confidence: 91%
“…Regarding educational level, we found that cancer patients with low educational levels had more depression, which is similar to the findings of other studies 31,32 . However, other publications did not show a significant difference between the two variables of education level and depression 19,33 .…”
Section: Discussionsupporting
confidence: 91%